Gendered discriminatory norms and academic performance disparity among senior high school students in Northwestern Ghana - Tobias Tseer; Frederick Ngmenkpieo; Agape Kanyiri Damwah (Cogent Education)
In the field of educational science, scholars have often alluded to the issues of gender parity in enrollment, transition and completion as well as general academic performance. Yet, the extent to which deeply entrenched heteropatriarchal practices and ideologies intersect to prompt varied academic outcomes for male and female students in mathematics is often overlooked. Investigating this phenomenon amongst a least studied population of senior high school students and within a highly heteropatriarchal society like the Upper West region provided new insights that not just contributes to existing literature but also informs policy formulation. A mixed-method approach was used as a methodological framework where data were generated through questionnaires, interview and discussion guides from 316 participants who were recruited through stratified and expert purposive sampling techniques. The analysis of the collected data revealed that normalized gender discriminatory practices and parental preferences for male children by parents serve as predictive factors for the varying academic achievement of male and female senior high school students in mathematics in the Upper West Region of Ghana. The study contributes new knowledge to literature by connecting normalized gender discriminatory practices to performance parity between male and female students in mathematics arguing that male students are poised to outperform their female counterparts for as long as culturally entrenched gender discriminatory practices and ideologies continue to favor them.